Burkholderia cepacia complex (Bcc) in goats: First report in Bangladesh - Abdullah Al Mamun; S. M. Sujan Ashraf; Amir Hamza Shuvo; Farhan Ibne Siddique; Hasan Khan; Naeem Ahammed Ibrahim Fahim; Chandra Shaker Chouhan; Farzana Yeasmin; Md. Mahbub Alam; Md Tanvir Rahman; Md. Siddiqur Rahman (PLoS ONE, 2026)
The Burkholderia cepacia complex (Bcc) comprises a diverse group of opportunistic pathogens that are critically relevant to human and animal health. Bcc induces life-threatening infections of the lung in human patients with cystic fibrosis and chronic granulomatous disease and causes mastitis and abscesses in sheep and goats. Therefore, this research aimed to identify the presence of Burkholderia cepacia complex (Bcc) in goats in Bangladesh using serological tests such as the Glanders Rapid Detection Test Kit (GRDTK) and Enzyme-linked immunosorbent assay (ELISA) and molecular tests such as PCR, Sanger sequencing, and phylogenetic analyses. A total of 40 goat blood samples were collected, comprising 30 samples from goats exhibiting a history of abortion accompanied by respiratory symptoms and 10 samples from clinically healthy control goats. Among the 30 samples from symptomatic goats, eight isolates (26.67%) were observed to grow in Luria-Bertani broth, while there was no growth from the control group. Five (62.50%) were found positive for bacterial presence when analyzed using the 16S rRNA gene-specific PCR assay for broth-positive samples. In the Genomix GRDTK and ELISA tests, six isolates were identified as positive for Burkholderia spp. Of the eight broth culture-positive samples, two (25%) were found to be positive by genus-specific PCR using groEL primers and species-specific amplification using zmpA primers. Phylogenetic analysis of positive goat samples confirmed the presence of the Bcc, which showed 100% similarity with the strains from India, Japan, and China. The discovery is the first detection of Bcc in animals in Bangladesh. It raises significant concerns for animal and public health. These findings highlight the critical need for strengthened diagnostic strategies, improved microbiological surveillance, and further research into Bcc’s epidemiology and zoonotic potential within the One Health framework to understand better and mitigate its zoonotic risks.